Rhynchocyrtus gen. nov. (Collembola, Entomobryidae) from the Southeast and Northeast Brazilian regions - de Mendoça, Maria Cleide; Fernandes, Liliane Henriques (Zootaxa, 2007)
Rhynchocyrtus gen. nov. is described and illustrated with a new type species: Rhynchocyrtus klausi sp. nov. from National Park of Tijuca (Rio de Janeiro, RJ, Brazil). This work also includes a new record of Rhynchocyrtus gen. nov. and a new species from a remnant rainforest area of the Northeast region, in Pernambuco State, Brazil.